Total bed-material discharge in alluvial channels - Chang, Feng-Ming, author; Simons, Daryl B., author; Richardson, Everett V., author (Colorado State University. Libraries, 1965)
A study of total bed-material discharge in alluvial channels, partially based on existing theories, has been conducted. The bedload discharge was obtained by utilizing the energy-work relation of the fluid and the bed material. An equation for velocity distribution was obtained by integrating the Reynolds equations using Prandtl's Hypothesis of mixing length. Applying the basic equation for the distribution of suspended load by O'Brien, the suspended bed-material discharge was investigated in terms of bedload discharge. Then, the total bed-material discharge was obtained simply by adding the bedload discharge and the suspended bed-material discharge. The results through checking with available laboratory and field data appeared to be mutually consistent and satisfactory.
CER65FMC-DBS-EVR3.
At head of title: International Association for Hydraulic Research.
Keywords: Sedimentation and deposition; Sediment transport